Hyperglycemia Induces Neutrophil Extracellular Traps Formation Through an NADPH Oxidase-Dependent Pathway in Diabetic Retinopathy - Wang, Luoziyi; Zhou, Xin; Yin, Yizhou; Mai, Yuxin; Wang, Desai; Zhang, Xuedong (Frontiers in Immunology, 2019)
Neutrophil extracellular traps (NETs), the product of NETosis, is found to localize pathogens and crystals in immune response. Recent studies have found that excessive NETs lead to disease conditions such as diabetes and its complications like diabetic retinopathy (DR). However, the correlation between NETs and high glucose or DR remains unclear. Here, we found NETs level was significantly increased in the serum of diabetic patients, especially in proliferation diabetic retinopathy (PDR) patients. High glucose dramatically increased NETs production in diabetic individuals with time prolonging. The activation of NADPH oxidase was involved in the NETs process which is triggered by high glucose. Moreover, we verified the infiltration of neutrophils in the eyes and adhesion to vascular endothelial cells in diabetic rat models. NETs formation was observed in the vitreous bodies and retinas of diabetic individuals, which indicates NETs may play a role in the pathogenesis of diabetic retinopathy. Furthermore, anti-VEGF therapy downregulates NETs production indicating that NADPH oxidase-derived ROS may be another signaling pathway involved in anti-VEGF therapy.